Adherence to Fluid Restriction in Hemodialysis Patients at RSUD Ibu Fatmawati Soekarno Kota Surakarta - Irma Mustika Sari; Erika Dewi Noorratri; Dian Setyawan (Promotif : Jurnal Kesehatan Masyarakat, 2024)
Background: Excessive fluid intake due to non-adherence leads to a decreased quality of life in hemodialysis (HD) patients and even death. The increasing incidence of chronic kidney failure is a progressive condition affecting more than 10% of the global population, or over 800 million people. One of the common problems faced by hemodialysis patients is non-adherence to fluid intake restrictions. This non-adherence can lead to fluid overload in the body, resulting in complications of chronic kidney disease. The objective of this study is to identify the most influential factors affecting the adherence of hemodialysis patients to fluid restriction. Method: The research method employed a quantitative approach using a cross-sectional design. Data was collected using a questionnaire and analyzed using Kendall's tau test Result: Kendall’s tau analysis indicated that while there was no significant relationship between age, marital status, and fluid adherence, there were significant correlations between gender, education level, occupation, and duration of hemodialysis and fluid adherence. Conclusion: Gender, education level, occupation, and duration of hemodialysis were significantly associated with fluid adherence among hemodialysis patients at RSUD Ibu Fatmawati Soekarno Surakarta.